2012
DOI: 10.1590/s1517-83822012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Imipenem-resistant Acinetobacter baumannii carrying the ISAba1-bla OXA-23, 51 and ISAba1-bla ADC-7 genes in Monteria, Colombia

Abstract: The purpose of this study was to identify the genes coding for resistance to ceftazidime and imipenem and describe the molecular epidemiology of A. baumannii strains isolated from a clinical center in Colombia. Twenty isolates of imipenem-resistant A. baumannii from an equal number of patients with nosocomial infections were obtained. Primers were used to amplify genes blaIMP, blaVIM, blaOXA-23, blaOXA-24, blaOXA-58, blaOXA-51 and blaADC-7. To detect insertion sequences ISAba1/blaOXA-23, ISAba1/blaOXA-51 and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
1
14
1
5
Order By: Relevance
“…baumannii complex. However, resistance to carbapenems has increased, thereby limiting the use of this class of antibiotics (15) . The present study demonstrated that the presence of the ISAba1 promoter sequence associated with the bla OXA-23-like gene in A. calcoaceticus-A.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…baumannii complex. However, resistance to carbapenems has increased, thereby limiting the use of this class of antibiotics (15) . The present study demonstrated that the presence of the ISAba1 promoter sequence associated with the bla OXA-23-like gene in A. calcoaceticus-A.…”
Section: Discussionmentioning
confidence: 99%
“…Higher carbapenem hydrolysis rates have been reported to result from the acquisition of insertion sequences (ISs) that affect the expression of the bla OXA genes encoding oxacillinases (10) (11) (12) (13) (14) . These elements are the smallest and most abundant transposable elements and are capable of causing mutations and rearrangements in the genome, thereby contributing to the spread of resistance and virulence determinants in various bacterial species (15) . Different ISs have been described in the A. calcoaceticus-A.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations